The investigation of transesterification effect of Eruca sativa Madwort's oil as biodiesel on performance and emissions of internal combustion engines. Issue 17 (2nd September 2021) - Hajinezhad, Ahmad; MohammadHosseini, H.A.
ABSTRACT: As fossil fuel sources are being decreasing day by day, finding renewable energy resources are necessary. Biodiesel is one of the best alternatives in diesel engines. Eruca sativa Madwort (ESM), a nonedible plant and spice of Brassica carinata family, is one of the Iranian local oil seed plants that can grow in poor and unsuitable lands and has been used as an initial source of biodiesel in this study. Transesterification of ESM's oil has been done using KOH as catalyst and methanol with protection of molar proportion of oil to alcohol (1:6). Indirect Spray Diesel engine (Lister M8.1) is used according to ECE-49 standard and different proportions of diesel fuel and biodiesel (B0, B5, B10, B20, and B35) are selected to investigate functional parameters and exhaust emission. The results show that with the increase in the percentage of the amount of biofuel in the fuel mixture, the amount of NO, NOx, and soot contamination reduce. Also, the diesel engine has best specific fuel consumption equal to 470 g/kw.h at B20. Other basic engine parameters such as power also remain in optimal condition. Finally, it is shown that ESM has good potential to replace the diesel fuel in diesel engines, without major modification in the design of engine and injection system.